PENERAPAN MEDIA WORDWALL UNTUK MENINGKATKAN MINAT BELAJAR IPAS (ILMU PENGETAHAUN ALAM DAN SOSIAL) PADA PESERTA DIDIK KELAS IV UPT SPF SD INPRES MACCINI I/1: Penilitian Tindakan Kelas (PTK) - Winda Dwi Putri; Sri Aprilia Anwar; Hartono Bancong (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
In order to increase the learning interest of class IV students of UPT SPF SD Inpres Maccini I/1 in learning science (natural and social sciences) about plant body parts through the use of wordwall learning media is the purpose of this study. This study is a Classroom Action Research (CAR) which is carried out in 2 cycles with each cycle consisting of several stages, namely the planning, implementation, observation, and reflection stages. This study used research subjects, namely 20 class IV students of UPT SPF SD Inpres Maccini I/1. Observations, tests and documentation were used to collect data in this study. In this study, the results obtained stated that in cycle 1 the average score of learning outcomes using wordwall learning media was 82% in classical completeness. Meanwhile, when cycle 2 the average score of learning outcomes using wordwall learning media increased by 93% with very good completeness. Therefore, it can be concluded that students' learning interest in learning science (natural and social sciences) about plant body parts in class IV students of UPT SPF SD Inpres Maccini I/1 can increase with the application of wordwall media.